Systematics, phylogeny and evolutionary pattern of the hystricognath rodent Eumysops (Echimyidae) from the Plio–Pleistocene of southern South America - Olivares, Adriana Itatí (2015)
†Eumysops is a peculiar representative of the currently tropical family Echimyidae, which evolved in increasingly dry and cold Plio–Pleistocene environments of southern South America. The results of a systematic and stratigraphic review of the genus, and of phylogenetic analyses based on both morphology and a combined morphological–molecular dataset in the context of extant representatives, are presented here. Recognised diversity includes four previously described species plus a new one from the late Pliocene. These species form a well-supported monophyletic clade, sister to the late Miocene †Pampamys and the extant Thrichomys. The position of †Eumysops–†Pampamys–Thrichomys in a major clade including non-‘eumysopine’ echimyids constrains the traditional taxon Eumysopinae only to these three genera. Phylogeny and stratigraphic distribution of †Eumysops species suggest an essentially cladogenetic evolutionary pattern. Beyond this, a gradual directional change, involving increase in size and in molar hypsodonty, is shown by †Eumysops chapalmalensis as part of a late Pliocene faunal turnover interpreted as a local representation of the 2.5-Ma cooling global event. Distinctive skeletal and dental anatomy of †Eumysops, including large orbits, shortened braincase, marked hypsodonty and postcranial specialisations, would be a result of its southern history related to a particular palaeoclimatic context.